Multi-walled carbon nanotubes induce stronger migration of inflammatory cells in vitro than asbestos or granular particles but a similar pattern of inflammatory mediators. (August 2019) - Westphal, Götz A.; Rosenkranz, Nina; Brik, Alexander; Weber, Daniel; Föhring, Isabell; Monsé, Christian; Kaiser, Nina; Hellack, Bryan; Mattenklott, Markus; Brüning, Thomas; Johnen, Georg; Bünger, Jürgen
Abstract: Biopersistent pro-inflammatory fibers are suspected human carcinogens. Cytotoxicity and transcription of pro- and anti-inflammatory mediators of different fibers were investigated in functional relationship to chemotaxis in vitro as a model for fiber-induced inflammation of the lung. We challenged NR8383 rat macrophages with multi-walled carbon nanotubes (MWCNT) and various asbestos fibers. The resulting cell supernatants were than studied using the Particle-induced Cell Migration Assay (PICMA) and cytotoxicity was determined using the LDH test. Expression of inflammatory mediators was analyzed with qPCR and verified by ELISA. Chrysotile A and the rigid, needle-shaped NM-401 caused the strongest cytotoxic effects and the largest number of migrated cells. In contrast, the MWCNT NM-400, NM-402, and NM403 were apparently non-cytotoxic but induced pronounced cell migration showing a very steep dose response. However, the strength of cell migration and cytotoxicity of the asbestos fibers were correlated. The expression profile of inflammatory mediators was comparable, although cytotoxicity of the MWCNT NM-401 and NM-403 differed strongly. Induction of the corresponding proteins was confirmed for CCL2, CCL3, CXCL1, CXCL3, IL1RA ( IL1RN ), CSF1, GDF15 and TNFa. Chrysotile A and NM-401 induced much stronger chemotaxis than the non-fibrous particles reported in our previous study. Cytotoxic and chemotactic effects correspond to the induction of inflammatory mediators. Highlights: We describe an in vitro model that allows the investigation of the particle and fiber induced inflammation of the lung. Strong, dose dependent, and clearly differentiated chemotaxis in response to fibers is shown. Fiber induced chemotaxis is paralleled by induction of inflammatory mediators and can occur independently from cytotoxicity.